The Lived Experience of Chinese International Students in the U.S. An Academic Journey - Zhou, Yalun; Wei, Michael; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This book marks a departure from traditional assumptions concerning the deficiencies of Chinese international students in terms of learning and adapting. It employs phenomenological narrative inquiry and a small culture approach to investigate the evolved, fluid experience of pursuing a graduate degree in the U.S. at Blue Fountain University (a pseudonym for a mid-western university). Adopting an interdisciplinary perspective, this book addresses two fundamental questions: What study abroad is and what study abroad counts? The sociocultural dimensions that shape the cross-border degree seeking endeavors inform stakeholders what works for Chinese international students$1 (Bsuccessful pursuits as EFL learners and ESL users and what could be improved. This book shares thoughts on the implications and impact of educational contexts to stakeholders at normal and dynamic contexts interrupted by global pandemic outbreak. It contributes to the understanding of the internationalization of the host institute and the EFL education reform efforts (policy making, teacher education, and classroom practice) in China (and in Asia at large).s
Chapter 1. Introduction and Background -- Chapter 2. The Lived Experience from China to the U.S.: A Sociocultural Roadmap -- Chapter 3. The Making and Remaking of the Chinese international Students: Perceptions as L2 Learners/Users -- Chapter 4. Understanding the Lived Experiences: A Poststructuralist Interpretation -- Chapter 5. Thoughts to Stakeholders in the Eye of the Beholders -- Chapter 6 Conclusions and Thinking to the Future.
Keywords: Language and languages$1 (BStudy and teaching.s; 9; Comparative education; Education, Higher; Language Education; International and Comparative Education; Higher Education